Low Level Helium-Neon Laser Therapy For Chemoradiotherapy Induced Oral Mucositis In Oral Cancer- A Systematic Review - Prashanthy.M.R, DineshDamodhar, Suganya.P,Bharathwaj.V.V, Sindhu.R, Prabu.D ,Shreelakshmi.S,Rajmohan.M (Drugs and Cell Therapies in Hematology, 2021)
AIM This study aims to examine the effects of low-level helium-neon laser therapy in the prevention and treatment of Oral cancer therapy-induced oral mucositis. METHODOLOGY A systematic review of controlled trials, clinical trials, and a pilot study was performed. Electronic and hand searches retrieved 5113 records.1204 were screened. Six studies were included in the systematic review.Study included in the systematic review examined the intervention and outcomes. RESULTS In this systematic review , four studies were included, which were randomized controlled trials and pilot studies. There were studies performed in different countries. Oral mucositis was significantly (p< 0.02) reduced after low level helium-neon laser therapy were compared with placebo group. This preventive effect of low level helium-neon laser therapy improved with adequate doses above 1 -4J were included. For the treatment of Oral mucositis (OM) ulcers, the number of days with OM grade 2 or worse was significantly reduced after induced the low level helium-neon laser therapy for four days less than the placebo group. CONCLUSION There is consistent evidence from high quality studies that Low level helium-neon laser therapy were partly prevented the development of oral cancer therapy-induced oral mucositis. Low level helium-neon laser therapy also significantly reduced pain, severity and duration of symptoms in patients with oral cancer therapy-induced Oral mucositis.